Pain Relief - From Analgesics to Alternative Therapies 2017
DOI: 10.5772/66649
|View full text |Cite
|
Sign up to set email alerts
|

Paracetamol: Update on its Analgesic Mechanism of Action

Abstract: Paracetamol is the most widely used over-the-counter medication in the world. The mechanism of action of its analgesic effect was often considered as based on the mobilization of the cyclooxygenases and more recently on serotonergic pathways. A new metabolic pathway involving the generation of an active metabolite, AM404 (N-(4-Hydroxyphenyl)-5Z,8Z,11Z,14Z-eicosatetraenamide), in the brain by the fatty acid amide hydrolase (FAAH) enzyme, was recently identified. This chapter describes experimental data that hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Speculations on the neurochemical substrates of our findings are also limited by what we know about acetaminophen’s exact neurochemical mechanism of action which remains contentious. Past research has suggested a prostanoid mechanism (Flower and Vane, 1972), while more recent experimental evidence suggests that a combination of endocannabinoid, vanilloid, and serotonergic neurochemical mediators may also mediate effects of acetaminophen (Mallet et al., 2017). A central serotonergic mechanism would be a promising candidate to explain effects of acetaminophen on both positive and negative empathy (Mischkowski et al., 2016), as dispositional variations in serotonergic neurotransmission affect sensitivity to both positive and negative emotions of other people (Way and Keaveney, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speculations on the neurochemical substrates of our findings are also limited by what we know about acetaminophen’s exact neurochemical mechanism of action which remains contentious. Past research has suggested a prostanoid mechanism (Flower and Vane, 1972), while more recent experimental evidence suggests that a combination of endocannabinoid, vanilloid, and serotonergic neurochemical mediators may also mediate effects of acetaminophen (Mallet et al., 2017). A central serotonergic mechanism would be a promising candidate to explain effects of acetaminophen on both positive and negative empathy (Mischkowski et al., 2016), as dispositional variations in serotonergic neurotransmission affect sensitivity to both positive and negative emotions of other people (Way and Keaveney, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Such a finding is consistent with neurodevelopmental theories suggesting that the same physiological or genetic factors shape increased susceptibility to both positive and negative experiences (Boyce and Ellis, 2005; Belsky and Pluess, 2009). Though acetaminophen or its psychoactive metabolites do not directly interact with serotoninergic receptors, depleting serotoninergic activity in the brain reduces the analgesic effects of acetaminophen (Mallet et al., 2017). Psychological effects of acetaminophen, including on positive empathy, may rely on a similar serotoninergic mechanism, though such a mechanism awaits to be demonstrated conclusively.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Despite its wide use, debate exists regarding the analgesic mechanism of action (MoA) of paracetamol. 7 Historically, it was believed that the paracetamol-mediated analgesia stems solely from its cyclooxygenase (COX)dependent inhibitory effect on prostaglandin (PG) synthesis 8 ; however, it is now evident that the analgesic MoA of paracetamol is multidimensional and involves several pathways within the central nervous system (CNS), such as the endocannabinoid, serotonergic, and nitric oxide pathways [9][10][11][12][13][14] or for some authors opioid pathways. 15 The notion that we already know concerning the metabolic pathways for paracetamol has been challenged in the past two decades following the 2005 study by Högestätt et al; in this report, the authors demonstrated that, following hepatic deacetylation to p-aminophenol, this paracetamol metabolite crosses the blood-brain barrier (BBB) and is converted to N-arachidonoylphenolamine (AM404).…”
Section: Introductionmentioning
confidence: 99%
“…APAP is an analgesic and antipyretic agent that has little anti-inflammatory activity. It has been used clinically for more than a century, having been introduced into use in 1893 and is now the most widely prescribed analgesic in the world 33. APAP is commonly used for the relief of fever, headaches, and other minor aches and pains.…”
Section: Introductionmentioning
confidence: 99%
“…APAP undergoes a two-step metabolic process to reach the active metabolite (Figure 1). 36 APAP is first metabolized in the liver to p -aminophenol which is then metabolized in the brain by fatty acid amide hydrolase (FAAH) containing cells into N-(4-Hydroxyphenyl) arachidonylamide (AM404) 33,3640. AM404 is a potent agonist of the transient receptor potential vanilloid type 1 (TRPV 1 ),39 a low-affinity ligand of the cannabinoid receptor type 1 (CB1),36,41 an anandamide membrane transporter blocker,42 and a COX inhibitor 36.…”
Section: Introductionmentioning
confidence: 99%